(untitled) (Journal of Pharmaceutical Negative Results, 2021)
Introduction: An ancient form of traditional medicine, Ayurveda, is based upon the various forms of prakriti and has drawn scientific interestfrom medical professionals. Important scientific applications of discerning prakriti (body constitution) lie in predicting disease susceptibilityof an individual, and deciding disease prognosis and treatment of choice for it. This calls for inventing a universally applicable, standardizedtool for the analysis of Prakriti, which would be helpful to integrate Ayurvedic fundamentals with allopathic medicine.Objectives: To assess and compare cardiovascular autonomic function status in normal healthy individuals of various Ayurveda Prakritis.Methods: This cross sectional study was carried out on 79 randomly selected normalhealthy subjects in the age group of 18-40 years withdual constitutional prakriti types (Dvandvaja Prakriti). Various cardiovascular autonomic function tests were assessed in all these subjects.Results: Out of all the cardiovascular reflex tests, mean values for heart rate response to postural change (30:15 ratio) as well as heart rateresponse to deep breathing were found to be the highest in kapha dominant prakriti, though not statistically significant. Both these parametersdenote parasympathetic activity. Whereas, the mean value for heart rate response to Valsalva maneuver, which indicates both sympathetic andparasympathetic activity, was found to be the highest in vata prakriti though not statistically significant. Of all the tests done to evaluate theheart rate variability, the mean value for normalized high frequency (HFnu) which signifies parasympathetic modulation was again found tobe the highest in kapha dominant prakriti individuals, though not statistically significant.Conclusion: Our study results are suggestive of a parasympathetic predominance in normal healthy individuals with prakriti of kapha asprimary dosha.